The relationship between crop-related agricultural workload and maternal and infant nutritional status in rural Pakistan: the LANSA project. - Gazdar, Haris. (Tufts University. Tisch Library., 2017)
This presentation details a study which investigated women's workloads during pregnany and their associations with body mass index and nutritional status.